ERADICATING SUPERSTITIONS THROUGH LITERATURE: MAHASWETA DEVI AND HER LITERARY EXCELLENCE - Kumar, Satyam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This essay aims to examine the short tale Witch by Mahasweta Devi from the collection Bitter Soil (1998) from an ecofeminist standpoint, emphasizing the negative impacts of extra-activism, the system of bonded labour, and the exploitation of the environment and the underprivileged. In this short narrative, Devi eloquently depicts the subjugation of the tribal society, the exploitation of the environment, the outrages, and the prejudices of tribal women. Both the British Empire's pre-independence rulers and the mediaeval ancient kings drove tribal people from their ancestral lands; post-colonial India's development initiatives, like land conversion and forest degradation, made their complaints even worse. Devi fosters ecological consciousness and the coexistence of humans and nature in the selected work. According to the article, extra-activism is a more profit-driven concept that is indifferent to the harm done to both people and the environment. It also methodically examines how the narrative Witch contributes a fresh perspective to the current ecofeminist debate, drawing on a number of Western and Indian ideas that are even more eclectic.